(3QSGdI aj GdJhMjOs - (3eMeO Hf YHO GdaJGM GdHfcGHjfjs
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hGdUdGI hGdSdGe Ydi NjQ Ndbg eMeO hBdg CLeYjf s
(3BNQgG (B:s
(3Ef de jJUa HGdaYd Edi BNQg ef Cf eGfY GdGJUGa eGfY GdEecGf CjVkG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B9s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdcJhQ MSjf Ydj eMahX (B- (3HZOGO (B(195) s
Keywords: (3GdJhMjO hGdedd hGdfMds